PENGARUH PELATIHAN, KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN BAGIAN PENJUALAN DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI PADA PT. GULANG MEDICA INDAH PEKANBARU - Ernur, Muatir Muhammad Husen; ', Machasin; ', Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Human resources are the main capital in a company because the achievement of corporate objectives depends on the quality and quantity of its human resources. This study aimed to examine the effect of training, compensation and career development on employee performance and motivation of sales as a mediating variable in Gulang Medica Indah Pekanbaru Company. The population in this study were all employees of Gulang Medica Indah Pekanbaru Company sales totaling 33 people. Sampling in this study is to use the census method, which according to this method the entire population can be sampled. Data was collected by using a questionnaire. Methods of data analysis using path analysis. The results of the research to get the results that training, compensation, and career development of significant and positive impact on employee motivation and performance Gulang Medica Indah Pekanbaru Company. But motivation does not mediate the effect of training, compensation, and career development on employee performance. The results also show that there is no difference in the performance of the employee Gulang Medica Indah Pekanbaru Company by gender.Keywords : Training, Compensation, Career Development, Motivation and Performance